PENGEMBANGAN MEDIA PAPAN KANTONG PINTAR SAINTIFIK (PAKAPINSA) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DAN SIKAP ILMIAH PADA MATA PELAJARAN IPA SD KELAS III - Zufi Firda Alawiyah; Taufik Muhtarom (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a Scientific Smart Pocket Board (PAKAPINSA) learning media that is valid, practical, and effective in improving science process skills and scientific attitudes of third-grade elementary school students. This research employed the Research and Development (R&D) method using the ADDIE model, consisting of analyze, design, development, implementation, and evaluation stages. The subjects were third-grade students of public elementary school Gunung Mulyo. Data were collected through questionnaires, observation sheets, and tests. The results indicated that the PAKAPINSA media was categorized as highly valid based on expert validation. The practicality of the media was shown through positive responses from teachers and students. The paired sample t-test analysis showed a significance value of 0.000 < 0.05, indicating a significant improvement after implementation. The average score of science process skills increased from 50.75 to 65.65, while scientific attitudes improved from 68 to 87.93. Therefore, the PAKAPINSA media is considered valid, practical, and effective for elementary science learning.